Twins' and Singletons' Linguistic Environment: A Systematic Review - Trombetta, Tommaso; Brustia, Piera; Curti, Lorenzo; Caldarera, Angela M.; Gerino, Eva; Rollè, Luca (Frontiers in Psychology, 2019)
Background: Among twins, lower linguistic skills emerged when compared with singletons. Considering the association found between parental linguistic input and children’s language development, exploring the differences between twins and singletons’ linguistic environments could find variables that are potentially associated with the lower linguistic skills of twins. Aim: The current systematic review aims to analyze and systematize the existing literature focused on the comparison of twins’ and singletons’ linguistic environments within their first 3 years of life. Methodological issues (i.e., the procedure used to assess the linguistic environment, the coding of the linguistic environment’s features, the computational method employed to assess the parental linguistic input, and participant characteristics) and differences found among twins and singletons regarding their linguistic environment (i.e., linguistic input quantity, linguistic input complexity, linguistic features of child-directed speech, parental responsiveness and directiveness, joint attention, and book reading) were highlighted. Method: The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) statement was followed. Eligible studies were searched through EBSCO, PubMed, and Web of Science. From this search, 1,347 study results emerged, and 8 studies were included. Results: To our knowledge, this is the first systematic review focused on the comparison of twins’ and singletons’ linguistic environments. Differences between the groups were found in all the included studies. Data against twins were generally identified regarding all the considered linguistic environment’s features. However, conflicting results within and between the included studies emerged, mainly according to the computational method employed (i.e., twin moms value, twin direct dyadic value, twin direct dyadic + both value, and input directed toward both children simultaneously). Conclusion: The disadvantaged linguistic environment of twins is likely due to limited parental resources and demands associated with the management of two children of the same age. However, the limited and conflicting data found did not allow for a firm conclusion to be drawn on the differences in the twins’ and singletons’ linguistic environments. Further studies on the topic are needed.